2020
DOI: 10.1111/ajt.15757
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of health-related quality of life among renal transplant patients associated with graft failure and symptom distress: Analysis of the BENEFIT and BENEFIT-EXT trials

Abstract: Understanding the correlation between transplant symptoms, health‐related quality of life (HRQoL), and graft outcomes is needed to support patient‐focused drug development and posttransplant management. A post‐hoc analysis of patient‐reported outcomes from the Phase III belatacept trials was conducted in order to investigate the interrelationship between trajectories of HRQoL, symptom experience, and allograft outcomes. HRQoL and symptom experience were evaluated using Short‐Form 36 Survey (SF‐36) and Modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…Consistent with previous reports, this finding confirms the important impact that adverse symptoms can have on a patient’s well-being. 3,4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with previous reports, this finding confirms the important impact that adverse symptoms can have on a patient’s well-being. 3,4…”
Section: Discussionmentioning
confidence: 99%
“…Our results also seem to be in line with prior literature, in that female respondents reported more symptoms and a higher perceived distress than men. 4,17…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, by integrating patient-reported outcomes (PROs) into clinical systems, the patient voice can be indirectly captured through data, highlighting areas in need of improvement such as side effects or challenges adhering to complex regimens [26]. For example, PROs from clinical trials have shown high rates of symptoms post-transplant including and mental health-related symptoms (e.g., depression, anxiety, and fatigue) [27]. Development and validation of measures for transplant-related and donation-related PROs should be a patient advocacy priority.…”
Section: Include the Patient Voice In Healthcare Decision-making And mentioning
confidence: 99%